1984
DOI: 10.1002/1097-4679(198409)40:5<1170::aid-jclp2270400508>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between strategies of coping and perception of pain in three chronic pain groups

Abstract: Examined the relationship between perception of pain, personality, coping and the reactions of family members in three chronic pain groups (sickle cell anemia, arthritis, and low back pain). Sixty black Ss equally distributed in the three medically diagnosed pain groups completed the McGill Pain Questionnaire, Maudsley Personality Inventory, a self‐control measure, and the modified spouse response questionnaire. Nonsignificant association was detected between measures of pain and neuroticism; a significant inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…[28][29][30] For example, Keefe et al 1 compared patients with rheumatoid arthritis pain to patients with chronic low back pain and myofascial pain and found that although patients with rheumatoid arthritis pain reported more frequent use of the pain coping strategies measured by the CSQ, they used less catastrophizing compared to the other 2 groups. Furthermore, it has been reported that different pain diagnostic groups used different types of pain coping strategies, 1,31 and different pain coping strategies may be differentially adaptive for different pain problems. 32 It might be expected that it is the coping strategies used rather than pain site or diagnosis, per se, that are likely to influence adjustment, as was recently demonstrated by Carroll et al 33 But in view of Keefe et al's earlier findings, it needs to be demonstrated that Affleck et al's findings are replicable in other pain populations.…”
Section: Neuroticism and Pain Coping Strategiesmentioning
confidence: 99%
“…[28][29][30] For example, Keefe et al 1 compared patients with rheumatoid arthritis pain to patients with chronic low back pain and myofascial pain and found that although patients with rheumatoid arthritis pain reported more frequent use of the pain coping strategies measured by the CSQ, they used less catastrophizing compared to the other 2 groups. Furthermore, it has been reported that different pain diagnostic groups used different types of pain coping strategies, 1,31 and different pain coping strategies may be differentially adaptive for different pain problems. 32 It might be expected that it is the coping strategies used rather than pain site or diagnosis, per se, that are likely to influence adjustment, as was recently demonstrated by Carroll et al 33 But in view of Keefe et al's earlier findings, it needs to be demonstrated that Affleck et al's findings are replicable in other pain populations.…”
Section: Neuroticism and Pain Coping Strategiesmentioning
confidence: 99%
“…Nevertheless, a number of studies have demonstrated the expected association between patient reports of spouse solicitous behaviours and greater levels of pain intensity. 11,14,24,[27][28][29][30][31][32] Yet the relationship between the two variables is not straightforward, and one of the factors that appears to mediate the link between them is the type of chronic pain disorder, or, more accurately, partner beliefs about the validity of the chronic pain problem. Anderson and Rehm 27 showed that pain patients with an unambiguous medical diagnosis (rheumatoid arthritis, sickle cell disease) reported a decrease in solicitous responding from spouses during increases in pain.…”
Section: Pain Intensitymentioning
confidence: 99%
“…Pain is the primary indicator of health perceptions of patients and clinicians [9], and while it is seen as largely a sensory experience, there is a growing, albeit causally unclear, body of research that suggests a strong link between pain and depression. Some studies suggest that pain leads to depression [10,11], while others suggest that depression leads to pain [12,13].…”
Section: Introductionmentioning
confidence: 99%